EFEK MODERASI KEPUASAN KONSUMEN PADA PENGARUH HARGA DAN KUALITAS TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA - Dewi, Maria Kristina; Rahadhini, Marjam Desma (Universitas Slamet Riyadi, 2013)
ABSTRACT The purpose of this research was to examine the significance of the influence of price and quality on customer satisfaction with the purchasing decision as a moderating variable. The population in this research is that consumers who buy Honda motorcycles at Dealer Timbul Jaya Motors Sukoharjo in December 2011, considering the population of many consumers, it is 50 sample taken consumers by using accidental quota sampling. Data analysis techniques used multiple linear regression analysis, t test, F test, testing the absolute value of the difference and the coefficient of determination. The result of t test indicate that price, quality, customer satisfaction have significantly effect to purchase decision. F test results obtained p value 0,000 < 0,05 is indicate that the model is fit. Test of the absolute values of the difference I obtained ABSZX1_ZX3 0,238 > 0,05, adjusted R square is 0,410. This means that if there is an influence on the purchase decision variables at 41,0% can be explained by the price and customer satisfaction. Test of the absolute values of the difference II obtained ABSZX2_ZX3 0,126 > 0,05, adjusted R square II is 0,473. This means that if there is an influence on the purchase decision variables at 47,3% can be explained by quality and customer satisfaction. The conclusion of this research is that customer satisfaction did not moderate the effect of price and quality of the purchase decision. Keywords: price, quality, customer satisfaction, purchase decision